Aktivitas Komunikasi Ritual Pada Tradisi Omed-Omedan Banjar Kaja Sesetan Denpasar Bali - Ni Putu Ayudiah Sriwidya Naraswari; Agus Aprianti (Public Inspiration : Jurnal Administrasi Publik, 2021)
Bali is an island which has a lot of customs and unique traditions. One of the unique traditions is Omed-Omedan. It is a tradition of attraction carried out by members of Banjar Kaja. The aim of this attraction is to establish friendship among the others. The research purpose is to explain the ritual communication activities that occur in the implementation of the Omed-Omedan Tradition. In this study, the ethnographic study method of communication in qualitative research uses the constructivism paradigm. In this study the data were obtained by in-depth interviews, literature study and field observations. The results obtained are then analyzed, explained, and concluded. Then the conclution is of this research is the communicative situations that occurred in the tradition, is sacred, joy, a thick magical aura, and intimacy. The communicative events that occurred started with praying together, Dharma Santi, the main event, and the ritual procession. Communicative action describes the entire verbal and non-verbal communication as well as the existing symbols. The three elements of the research results are the keys in describing to discusses how communication activities and ritual communication processes that occur in the Omed-Omedan Tradition in Banjar Kaja Sesetan, Denpasar City.